1995
DOI: 10.1128/aac.39.11.2397
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and prevention of microbial colonization of catheters

Abstract: Slime-producing staphylococci frequently colonize catheters, and when they are embedded in biofilm, they become resistant to various antibiotics. In the study that is described, the comparative efficacies of vancomycin, clindamycin, novobiocin, and minocycline, alone or in combination with rifampin, were tested in an in vitro model of colonization. The model consisted of the modified Robbins device with antibiotic-impregnated cement filling the lumen of catheter segments. The synergistic combination of minocyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(122 citation statements)
references
References 28 publications
3
111
1
7
Order By: Relevance
“…These include device coating with antibiotics which is of two types -active and passive. In the active coating, the release of antimicrobial agents in high fluxes occurs to inhibit the initial adhesion of the bacteria, 25,26,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…These include device coating with antibiotics which is of two types -active and passive. In the active coating, the release of antimicrobial agents in high fluxes occurs to inhibit the initial adhesion of the bacteria, 25,26,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Kombinasyon tedavisinin direnci azalttığı belirtilmiştir. Bunlardan dolayı rifampisin, MRSA ile oluşan biyofi lm tabakasına karşı kombinasyon tedavisinde diğer antistafi lokokkal antibiyotiklerle birlikte en çok tercih edilen antibiyotik olmuştur 14,22 .…”
Section: Idsa (Infectious Diseasesunclassified
“…Minocycline and rifampin may help decrease the probability of developing bacterial resistance by inhibition of protein synthesis and inhibition of DNA-dependent RNA polymerase, respectively (Darouiche RO, et al 1999). In-vitro and in-vivo studies have demonstrated the effectiveness of minocycline in retarding the emergence of staphylococcal strains that are resistant to rifampin (Raad et al 1995). Short-term follow-up for this prosthesis enhancement shows statistical improvement in infection reduction for first time implant patients by a single surgeon .…”
Section: Fig 1 Ams Ambicor Two-piece Inflatable Penile Prosthesismentioning
confidence: 99%